The Role of the Saidina Ali Institute in Staging the Dzikir Bermadah Education on Lengkang Island, Belakang Padang Sub-district - Sofia Madonna; Ardipal Ardipal; Syeilendra Syeilendra (International Journal of Educational Dynamics, 2022)
Belakang Padang is one of the sub-districts in Batam City which is famous for having various types of art that are different from other regions and are a hallmark of the region. One of the traditional arts originating from Belakang Padang Sub-district and very famous for its uniqueness, skill, skill and second to none is Dzikir Bermadah from Lengkang Island. Dzikir Bermadah art is a Malay performing art that is highly developed at this time and has become the pride of the community, especially in Belakang Padang Sub-district as a medium for conveying aspirations through poetry that will be conveyed in this Dzikir Bermadah performance. As an island directly facing Singapore, this art is expected to be an asset that can attract tourists to always come to the islands in the Belakang Padang Sub-district. In preserving and developing the Dzikir Bermadah art, an institution that plays an important role is needed, namely the Saidina Ali Institute. The Saidina Ali Institute as a cultural institution has the role of managing local cultural diversity, preserving Malay culture in society as a legacy left behind, and passing on and developing Malay culture from generation to generation. In addition, the Saidina Ali institution also plays a role in the development of existing culture, both for development and as a regional asset in Belakang Padang Sub-district.